Konsep Pengetahuan Muhammad Baqir Shadr dan Karl R. Popper: Komparasi Teori Disposesi dan Falsifikasi - Windari (Academy of Education Journal, 2026)
Post-positivist epistemology remains trapped in an ongoing demarcation crisis: how to distinguish scientific knowledge from non-knowledge without dismissing metaphysics a priori. The principle of verification failed to provide clear boundaries while stigmatizing metaphysics as meaningless. Popper states that something is scientific if it is potentially falsifiable. Consequently, what cannot be falsified falls outside the scientific category. However, beneath the firmness of this criterion, Popper leaves a gap: the recognition that scientific observation is always laden with a preceding theoretical framework—opening space for non-empirical elements in knowledge production. This gap serves as a bridge toward Muhammad Baqir Shadr. Through disposition theory, Shadr provides a more fundamental foundation: the distinction between primary conceptions (from the senses) and secondary conceptions (produced by reason as a rational apprehension of universal realities such as causality). Secondary conceptions constitute the legitimate ground for metaphysics—products of reason that are valid and necessary conditions for any knowledge claim. The convergence between Popper and Shadr lies in the recognition that knowledge is not solely measurable by empirical standards, for the determination of scientific versus non-scientific always proceeds from rational reason—causality, identity, non-contradiction, and coherence. Metaphysics—including rationally formulated religious claims—possesses a clear foundation: a logical foundation and a source of hypotheses for science, while simultaneously serving as a condition of possibility for scientific knowledge itself. This foundation does not rest on falsifiability, but on its foundational role as a conceptual framework that provides the conditions for scientific reasoning. This study offers a paradigmatic revolution: transcending the rigid boundary of scientific/non-scientific toward a spectrum of rational knowledge encompassing both the empirical and the metaphysical equally, while opening the legitimacy of metaphysical rationality in modern scholarship.